1989
DOI: 10.1007/bf01354768
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory convection in a viscoelastic fluid through a porous layer heated from below

Abstract: The stability of a viscoelastic fluid in a densely packed horizontal porous layer heated from below is considered using an Oldroyd model. Critical Rayleigh number, wave number, and frequency for overstability are determined by applying the linear stability theory. It is shown that the critical Rayleigh number is invariant under all relevant boundary combinations. Also, it is found that the effect of elasticity of the fluid is to destabilize the system and that of porosity is to stabilize the same. The limiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…Herbert (1963) and Green (1968) were first to analyze the problem of oscillatory convection in an ordinary viscoelastic fluid of the Oldroyd type under the condition of infinitesimal disturbances. Later on, Rudraiah et al (1989Rudraiah et al ( , 1990 had studied the onset of stationary and oscillatory convection in a viscoelastic fluid of porous medium. Laroze et al (2007) have analyzed the effect of viscoelastic fluid on bifurcations of convective instability, he analyzed that the nature of the convective solution depends largely on the viscoelastic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Herbert (1963) and Green (1968) were first to analyze the problem of oscillatory convection in an ordinary viscoelastic fluid of the Oldroyd type under the condition of infinitesimal disturbances. Later on, Rudraiah et al (1989Rudraiah et al ( , 1990 had studied the onset of stationary and oscillatory convection in a viscoelastic fluid of porous medium. Laroze et al (2007) have analyzed the effect of viscoelastic fluid on bifurcations of convective instability, he analyzed that the nature of the convective solution depends largely on the viscoelastic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Convection of non-Newtonian fluids in a porous medium is of considerable importance in several fields of application such as oil recovery, food processing, and the spread of contaminants in the environment, and in various processes in the chemical and materials industries. The onset of thermal convection of a viscoelastic fluid-saturated porous medium was studied by many authors (Rudraiah et al 1989;Kim et al 2003;Yoon et al 2004;Malashetty et al 2006). Since elastic behavior is inherent in non-Newtonian fluids, oscillatory instabilities can set in before stationary modes.…”
mentioning
confidence: 99%
“…The corresponding problem in the case of a porous medium has also not received much attention. Rudraiah et al (1989) have studied the linear stability of a viscoelastic fluid in a densely packed porous layer using an Oldroyd model. It is found that the effect of elasticity of the fluid is to destabilize the system and that of porosity is to stabilise the same.…”
Section: Introductionmentioning
confidence: 99%